2017
DOI: 10.1002/anie.201707274
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of [18F]Fluoroarenes by Nucleophilic Radiofluorination of N‐Arylsydnones

Abstract: A practical method for radiofluorination of anilines with [18F]fluoride via N-arylsydnone intermediates is described. These precursors are stable, easy to handle and facilitate direct and regioselective 18F-labeling to prepare [18F]fluoroarenes. The value of this methodology is further highlighted by successful application to prepare an 18F-labeled neuropeptide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 77 publications
1
19
0
2
Order By: Relevance
“…Thus, modern radiofluorination methods have sought to generalize the arene scope for this transformation. Current strategies include 18 F-deoxyfluorination of phenols via uronium (11) and N-arylsydnone (12) intermediates; displacement of sulfonium salts (13); fluorodemetalation of preformed palladium or nickel arene complexes from the requisite aryl halides or boronic acids (14,15); and copper-mediated cross-coupling of preformed or in situ-generated aryliodoniums (16,17), aryl boronic acids (18), esters (19), and arylstannanes (20) (Fig. 1A).…”
mentioning
confidence: 99%
“…Thus, modern radiofluorination methods have sought to generalize the arene scope for this transformation. Current strategies include 18 F-deoxyfluorination of phenols via uronium (11) and N-arylsydnone (12) intermediates; displacement of sulfonium salts (13); fluorodemetalation of preformed palladium or nickel arene complexes from the requisite aryl halides or boronic acids (14,15); and copper-mediated cross-coupling of preformed or in situ-generated aryliodoniums (16,17), aryl boronic acids (18), esters (19), and arylstannanes (20) (Fig. 1A).…”
mentioning
confidence: 99%
“…Murphy and co‐workers developed N ‐arylsydnones as novel precursors for the 18 F‐labeling of arenes bearing electron‐deficient substituents (Scheme B) . It was found that the sydnone was not only inductively more electron withdrawing than the nitro group, but was also positioned away from the aryl plane and limited full resonance with the arene.…”
Section: Labeling Methods With Fluorine‐18mentioning
confidence: 99%
“…Murphy et al. entwickelten N ‐Arylsydnone als neue Vorstufen für die 18 F‐Markierung von Arenen mit elektronenarmen Substituenten (Schema B) . Es wurde festgestellt, dass das Sydnon nicht nur induktiv stärker elektronenziehend ist als die Nitrogruppe, sondern sich auch abseits der Aryl‐Ebene befindet und keine vollständige Resonanz mit dem Aren eingeht.…”
Section: Markierungsmethoden Mit Fluor‐18unclassified